2011
DOI: 10.1063/1.3640887
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and computational studies of matrix-isolated iso-CHBr3: Structure, properties, and photochemistry of iso-bromoform

Abstract: Iso-polyhalomethanes are known reactive intermediates that play a pivotal role in the photochemistry of halomethanes in condensed phases. In this work, iso-bromoform (iso-CHBr(3)) and its deuterated isotopomer were characterized by matrix isolation infrared and UV/visible spectroscopy, supported by ab initio and density functional theory calculations, to further probe the structure, spectroscopy, and photochemistry of this important intermediate. Selected wavelength laser irradiation of CHBr(3) isolated in Ar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(75 citation statements)
references
References 80 publications
(69 reference statements)
9
66
0
Order By: Relevance
“…This isomerization pathway could be termed 'roamingmediated', because it involves the migration of the incipient bromine fragment and leads to the iso product species; however, this could not be confirmed without comparison to the same reaction in the gas phase. The isomeric form occupies a shallow minimum on the potential energy surface (PES)-somewhat below the C-Br bond radical dissociation asymptote [12][13][14][15] -and has been proposed 16 to be accessible on the way towards molecular bromine from photoexcited bromoform in the gas phase. This isomerization pathway in the gas phase can only occur through the internal rearrangement of atoms, that is, directly and without the involvement of any other species.…”
mentioning
confidence: 99%
“…This isomerization pathway could be termed 'roamingmediated', because it involves the migration of the incipient bromine fragment and leads to the iso product species; however, this could not be confirmed without comparison to the same reaction in the gas phase. The isomeric form occupies a shallow minimum on the potential energy surface (PES)-somewhat below the C-Br bond radical dissociation asymptote [12][13][14][15] -and has been proposed 16 to be accessible on the way towards molecular bromine from photoexcited bromoform in the gas phase. This isomerization pathway in the gas phase can only occur through the internal rearrangement of atoms, that is, directly and without the involvement of any other species.…”
mentioning
confidence: 99%
“…A recent computational study of CHBr3 isomerization showed significant charge-separation character in iso-CHBr2-Br, which exhibits mixed covalent and ionic character, with (CHBr2) + Br -contributing the major (62%) resonance structures. 26 We therefore undertook calculations of the electronic character of the iso-forms of CCl4 and CHCl3, following an NBO analysis similar to that reported by George et al 26 and using the computational methods outlined in Section 2.2. Table 1: Calculated wavelengths of the electronic absorptions of the Cl-solvent (Cl-CCl4 and Cl-CHCl3) complexes and iso forms (iso-CCl3-Cl and iso-CHCl2-Cl) considered to give rise to the transient UV and visible bands evident in Fig.…”
Section: Uv and Visible Absorption Band Assignmentsmentioning
confidence: 99%
“…Our assignments are similar in spirit to the earlier literature, but more consistent with recent experimental and computational studies of other halogenated methanes such as bromoform (CHBr3). [24][25][26] Iso species of this type are important as reactive agents in solution:…”
Section: Introductionmentioning
confidence: 99%
“…4,[25][26][27] Cage-enhanced geminate recombination has significant yield to the iso products and these products have been observed in variety of different experiments. 3,25,26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Ultraviolet excitation of CH 2 BrI yields iso-CH 2 Br-I or iso-CH 2 I-Br following C-I or C-Br bond cleavage, respectively. These products are predicted to have transitions in the visible or near UV with very large oscillator strength (∼0.5).…”
Section: Introductionmentioning
confidence: 99%